Factors influencing e-payment loyalty in Thailand - Ladkoom, Kobthong; Thanasopon, Bundit (My University, 2018)
Essentially, e-commerce involves trading of goods and services by electronic means. Due to the popularity of e-commerce many electronic payment or e-payment services have been emerged to enable consumers to easier and faster make payment for products and services. In Thailand, the government is trying to push the National e-payment program to provide Thai people with a standardized electronic payment system. In this research in-progress article, the researchers reviewed the literature on e-commerce and e-payment loyalty aiming to identify important factors influencing e-payment adoption in Thailand. We are able to come up with a research model comprising of key factors such as privacy risk, acceptability, consumers' liability, perceived usefulness and confirmation. The model will be used to frame our data collection and analysis in our future research.
Keywords: E-commerce; E-payment; Loyalty